COVID19.BR: A Dataset of Misinformation about COVID-19 in Brazilian Portuguese WhatsApp Messages - Martins, Antônio Diogo Forte; Cabral, Lucas; Mourão, Pedro Jorge Chaves; de Sá, Ivandro Claudino; Monteiro, José Maria; Machado, Javam (Anais do Dataset Showcase Workshop (DSW), 2021)
Nowadays, our society suffers with a major issue that unfortunately is becoming more and more problematic, once again through social networks, that is the misinformation. The primary source of misinformation in Brazil is the messaging application WhatsApp. However, due to WhatsApp's private messaging nature, there still few misinformation data sets built specifically from this platform. In this context, building a data set of WhatsApp messages about COVID-19 in Brazilian Portuguese and label misinformation messages within it becomes a crucial challenge. In this work, we present the COVID-19.BR, a data set of WhatsApp messages about coronavirus in Brazilian Portuguese, collected from Brazilian public groups and manually labeled.